Clinical Outcomes of MRI-Guided Adaptive Brachytherapy for Each Fraction in Locally Advanced Cervical Cancer: A Single Institution Experience - Chi, Yunbo; Pan, Ying; Zhang, Ning; Han, Dongmei; Guo, Xin; Mao, Zhuang; Cheng, Guanghui (Frontiers in Oncology, 2022)
Purpose This study aims to evaluate clinical outcomes of MRI-guided adaptive brachytherapy (MR-IGABT) for each brachytherapy fraction in patients with locally advanced cervical cancer (LACC). Methods and Materials A retrospective analysis was performed on 97 consecutive patients with LACC treated with 44.0–50.4 Gy external beam radiotherapy (EBRT) ± concurrent platinum-containing chemotherapy followed by 4 × 7 Gy MR-IGABT between September 2014 and April 2019. Intracavitary (IC)/interstitial (IS)/hybrid intracavitary and interstitial (IC/IS) brachytherapy was used in MR-IGABT. Brachytherapy planning and dose reporting followed the GEC-ESTRO recommendations. Clinical outcomes including overall survival (OS), cancer-specific survival (CSS), progression-free survival (PFS), local control (LC), and treatment-related toxicity evaluated by the RTOG criteria were analyzed. Kaplan–Meier and univariable and multivariable Cox regression analyses were used to analyze the prognostic factor. Results Median follow-up was 21.1 months. Median dose to 90% (D90) of the high-risk clinical target volume (HR-CTV) was 91.7 Gy (range 76.7~107.2 Gy). Two-year OS, CSS, PFS, and LC were 83.5%, 84.1%, 71.1%, and 94.8%, respectively. Four patients (4.1%) suffered from grade 3 late gastrointestinal radiation toxicity, and no other grade 3 or greater radiation toxicity occurred. Initial HR-CTV was an independent factor of OS (p = 0.001, HR = 1.018/cm3), PFS (p = 0.012, HR = 1.012/cm3), and LC (p = 0.011, HR = 1.028/cm3). The HR-CTV D90 (p = 0.044, HR = 0.923/Gy) was an independent factor of PFS. Age was an independent factor of LC (p = 0.010, HR = 1.111/year). Conclusion For patients with LACC, MR-IGABT was effective and safe. It showed favorable LC, OS, and minimal toxicity. Moreover, initial HR-CTV, HR-CTV D90, and age were significant prognostic factors.